Die-less clinching process and joint strength of AA7075 aluminum joints. (November 2017) - Sabra Atia, Mostafa K.; Jain, Mukesh K.
Abstract: AA7075 aluminum alloy sheets in different temper conditions (O, W and T6) were joined by die-less clinching. The material flow behavior, neck thickness and interlock characteristics during clinching were investigated by metallographic observations of clinched, cut and mounted samples. Blank holders of different shapes and dimensions were used to control the material flow. The effects of blank holder geometric parameters as well as forming forces on the shape of the formed interlock in clinching were studied. The highest strength temper state (T6) was shown to possess poor clinch-ability as it failed to clinch under most clinching conditions. This was attributed to its poor ductility and formability at room temperature compared to the other tempers. Lastly, mechanical performance of the formed joints was characterized by conducting single shear lap as well as peel tests. Various failure modes were observed for the different clinching conditions and material temper states. Highlights: Temper state of AA7075 aluminum alloy has a large effect on material flow behavior in clinching. Restricted material flow in the axial direction towards the end of the clinching process has a large influence on material interlocking. The blank holder groove depth and diameter affect interlock development and reduction in neck thickness respectively. Peel strength of the die-less clinched joint is largely affected by the interlock depth and not by neck thickness.